Preservative treatment of green rubberwood(Hevea brasiliensis) by vacuum-pressure impregnation - Tan A G; Chong K W; Tam M K (Malaysian Forester, 1983)
The treatment trials, aimed at establishing the feasibility of impregnating green sawn Rubberwood with preservatives by the vacuum-pressure process, were carried out. The test pieces were treated with solutions of borax pentahydrate of different concentrations. To control sapstain infection in the treated wood during seasoning, the solutions were incorporated with an anti-sapstain chemical. The results obtained show that green Rubberwood can be successfully treated with preservatives by the above-mentioned process. Using a 3;w/w borax pentahydrate solution, treatment of the sawn timber may be carried out within a few days of conversion. For thicker wood pieces, it is advisable to allow them to air-season for a week or longer before being kiln-dried to ensure that their cores are adequately loaded with the preservative.
Keywords: Green rubberwood; Rubberwood; Rubberwood preservation